The role of renewable energy in achieving water, energy, and food security under climate change constraints in South Asia - Neupane, Nilhari; Chaudhary, Pashupati; Rijal, Yashoda; Ghimire, Bishal; Bhandari, Roshan (Frontiers in Sustainable Food Systems, 2022)
The energy demand in South Asia is increasing at a rapid rate and is becoming harder to fulfill due to conventional energy sources’ expense, unsustainability, and high emissions. South Asia is a region with a high potential for renewable energy, especially in hydropower, that has yet to be tapped into. The lack of utilization of the full potential of renewable energy by the nations in this region has highly compromised the food, water, and energy security of the people. This article identifies the roles of renewable energy sources for achieving energy, water, and food security for nations in the South Asian region and provides suggestions for further development in the utilization of renewable resources. The article also identifies the potential for the development of hydropower and other renewable energy sources as well as opportunities and potential challenges for multilateral energy trade for increasing the availability of energy. This article suggests possible solutions for the promotion of hydropower and other renewables in South Asia through different approaches. The nexus approach for integrated planning, policy coherence, and institutional harmonization one of the approaches focused on in this article which helps to increase the benefit by reducing the transaction costs, generating additional synergies, and reducing the trade-off at different scales. These approaches will help for mitigating several challenges faced in the process of securing energy, food, and water security. A secured supply of food, water, and energy improves the quality of life in the region, improves the infrastructural development process in the region.